To rewrite the equation \(\frac{4x}{3x - 12} + 3 = 10\) in two equations joined by "and," we can isolate each part of the equation as follows:
-
Start with the original equation: \[ \frac{4x}{3x - 12} + 3 = 10 \]
-
Rearrange the equation to separate the fraction from the constant: \[ \frac{4x}{3x - 12} = 10 - 3 \]
-
Simplify the right-hand side: \[ \frac{4x}{3x - 12} = 7 \]
Now, we can express the original equation as two equations joined by "and": \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 10 - 3 = 7 \]
So the final representation is: \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 7 = 7 \]